2008
DOI: 10.1007/s11113-008-9100-y
|View full text |Cite
|
Sign up to set email alerts
|

Migration Within the Frontier: The Second Generation Colonization in the Ecuadorian Amazon

Abstract: Since the 1970s, migration to the Amazon has led to a growing human presence and resulting dramatic changes in the physical landscape of the Northern Ecuadorian Amazon frontier, including considerable deforestation. Over time, a second demographic phenomenon has emerged with the children of the original migrants leaving settler farms to set out on their own. The vast majority have remained in the Amazon region, some contributing to further changes in land use via rural-rural migration to establish new farms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 46 publications
4
76
0
13
Order By: Relevance
“…In bivariate analysis age (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), poverty, and residence of 10 years or less were associated with migration before diagnosis with leprosy (Table 1).…”
Section: Factors Associated With Migration In the Five Years Before Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In bivariate analysis age (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), poverty, and residence of 10 years or less were associated with migration before diagnosis with leprosy (Table 1).…”
Section: Factors Associated With Migration In the Five Years Before Dmentioning
confidence: 99%
“…Migration is most often associated with the movement of young adults, typically males between the ages of 20 and 35, who migrate for employment 14,19,30,31 . We found that migration of leprosy-affected individuals was significantly associated with being male after diagnosis, and overall, migrants were slightly older than the younger age-set typical of migration globally.…”
Section: Key Demographicsmentioning
confidence: 99%
“…VanWey (2003) showed that households in Nang Rong, Thailand pursued temporary migration as a form of income diversification, with the size of land holdings affecting the probability of migration differentially for male and female migrants. Barbieri et al (2009) additionally found that community-level context, including access to road networks, health centers, and schools affects the balance of rural-rural and rural-urban migration. Although road networks were found to increase rural-urban migration, increased road access is also associated with increased off-farm employment opportunities in rural areas.…”
Section: Introductionmentioning
confidence: 97%
“…Although road networks were found to increase rural-urban migration, increased road access is also associated with increased off-farm employment opportunities in rural areas. Increased access to health services appeared to reduce out-migration (Barbieri et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A unidade doméstica não depende exclusivamente da disponibilidade de mão de obra familiar, havendo um arranjo complexo que envolve troca de serviço (compadrio), venda própria da mão de obra e contratação, forte relação familiar, interface rural-urbana e uso da terra em propriedade distinta. A fecundidade deixa de ser importante como variável explicativa, estimulando uma nova frente investigativa que considera os elementos da contemporânea realidade dos ambientes pós-fronteira (BARBIERI; CARR; BILSBORROW, 2009;VANWEY;LUDEWIGS, 2011;GUEDES et al, 2011;VANWEY;VANWEY et al, 2006).…”
unclassified